Longitudinal analysis of changes in weight and waist circumference in relation to incident vasomotor symptoms: the Study of Women's Health Across the Nation (SWAN). Issue 1 (January 2017) - Gold, Ellen B.; Crawford, Sybil L.; Shelton, Janie F.; Tepper, Ping G.; Crandall, Carolyn J.; Greendale, Gail A.; Matthews, Karen A.; Thurston, Rebecca C.; Avis, Nancy E.
Abstract: Objective: Greater body mass index (BMI) and body fat are associated with vasomotor symptoms (VMS). Thus, weight loss may prevent VMS. We analyzed whether concurrent BMI or waist circumference and/or changes in weight or waist circumference predicted incident VMS and whether these relations differed by menopause stage or race/ethnicity. Methods: Data from 10 follow-up visits for 1, 546 participants in the Study of Women's Health Across the Nation who reported no VMS at baseline were modeled for time to first symptomatic visit in relation to concurrent BMI and waist circumference and change in weight and waist circumference during early and late menopause using discrete survival analyses, adjusting for covariates. Results: Greater concurrent BMI and waist circumference were significantly related to greater any and frequent (≥6 d in the last 2 wk) incident VMS in early menopause and lower VMS risk in late menopause. Percentage weight change since baseline and since the prior visit was unrelated to incident any VMS in either menopause stage. Percentage weight change since baseline had a significant shallow U-shaped association with incident frequent VMS in early menopause ( P = 0.02), a shallow inverse U-shape in late menopause ( P = 0.02), and a significant interaction with menopause stage ( P = 0.004) but not with race/ethnicity. Recent weight change was unassociated with incident VMS in either menopause stage. Results were similar for waist change. Conclusions: Concurrent BMI and waist circumference were positively related to incident VMS in early menopause and negatively related in late menopause. Maintaining healthy weight in early menopause may help prevent VMS.